Rancang Bangun Sistem Informasi Modul Procurement pada Aplikasi PT Jala Informatica dengan Bahasa Pemrograman Adobe Coldfusion - Rudi Sutomo; Ahmad Rizqi Nugraha (Unversitas Muhammadiyah Riau, 2022)
Recording an item is often fraudulent, for example, misuse of company assets with false statements to present financial statements from the accounting division so that this can be declared a criminal act of corruption. To avoid the act of cheating, a web-based application was created to be used by admins and users so that it would later become an information system for recording a procurement of goods. The procurement system for the success of the ERP system that focuses on the procurement module is based on the Coldfusion Family. This study aims to determine the success of the CORE-ERP system owned by PT Jala Informatica by creating a system designed for the procurement module with the prototyping method. Some testing systems are by the UAT standard with the blackbox method black box is based on the appearance and function of the existing features on the system. the test results on purchase orders, upload items, approvals, and general receive notes are declared successful.